Motivational Climate as Psychological Needs Fulfillment for Adolescent Athletes - Ni Putu Abigail Firsta S; Utami, Margaretha Sih Setija (Department of Guidance and Counseling, FIP, Undiksha, 2025)
Motivational climate is a key socio-cognitive factor contributing to the success of adolescent athletes in their sports careers. Social agents such as parents, coaches, and peers play a significant role in shaping motivational climates that support the fulfillment of athletes’ psychological needs. This study aims to analyze the types of motivational climates established by the social environment of adolescent athletes, evaluate the contributing factors to their development, and examine the psychological impacts of these climates on adolescent athletes. This research employed a literature review method using the PRISMA approach and reviewed ten relevant scholarly articles. The findings reveal two primary types of motivational climate: mastery climate, which is task-oriented, and performance climate, which is ego-oriented. The development of these climates is influenced by the behavior of social agents, group dynamics, task structures, and both physical and psychological factors. A positive motivational climate enhances athletes' self-concept and supports the fulfillment of basic psychological needs, namely autonomy, competence, and relatedness. The study concludes that a well-established motivational climate can serve as a crucial psychological foundation for the sustainable development of adolescent athletes’ potential and performance.